Kajian Kepatuhan Vaksinasi Covid-19 Berdasarkan Jenis Pekerjaan Masyarakat: Strategi Edukasi Tingkatkan Vaksinasi Di Kelurahan Lateri Kota Ambon - Pattinasarany, Camelia Gracia; Matauseja, Hosyiana Putri; Wambrauw, Deansatya Febrian; Kapuate, Yandris; Nindatu, Maria (Jurnal Karya Abdi Masyarakat, 2021)
Until now, there are still many people who do not want to be vaccinated on the grounds that they do not have an interest/job that requires them to be vaccinated. Based on data from the COVID-19 Vaccine Acceptance Survey in Indonesia in 2020, it shows that the majority of respondents who have knowledge of vaccines are those who work as civil servants (PNS, army/police, BUMN staff members, BUMD staff) of 80% with a vaccine acceptance rate by 70%. Followed by self-employed respondents and private workers. The lowest number is in respondents who do daily work, drivers, and ART/IRT by 44-46%. Vaccination data collection activities using the interview method by giving a set of questions contained in the questionnaire to the community which were carried out door to door in the houses of Lateri Village residents by KKN Students Batch XLVIII, Pattimura University Ambon in 2021 Lateri Village. This activity was carried out twice, namely on 21-22 October 2021 and 26-28 October 2021. The purpose of this activity was to find out the number of Lateri residents who had and had not been vaccinated. In this data collection activity, the population classified as Lateri Village residents aged 12 years and over. The sample technique is non-probability sampling in the form of accidental sampling. Based on the research data above, it can be concluded that there is a relationship between work and the level of compliance with COVID-19 vaccination in Lateri Village.